2013
DOI: 10.1177/0021998312470471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitric acid treatment time on the mechanical and surface properties of high-strength carbon fibers

Abstract: High-strength carbon fibers were treated with nitric acid and periodically analyzed by several different methods to develop an understanding of overall property changes and how they relate to composite design. Fiber diameter, tensile strength, surface morphology, surface chemistry and surface energy were all evaluated as a function of treatment time and two distinct stages of change were identified; the first characterized by surface modification and the second by carbon material loss. Initially, the tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Therefore, we conclude that the moderate acid treatment can improve shown in Figure 7. Overall, the Young's modulus decreased slightly after acid oxidation; the decline is due to acid etching that removes microvoids and the amorphous outer layer from the carbon fibre surface [15]. Some researchers mentioned also another potential mechanism of the modulus variation: a change in the orientation of crystallites in CFs [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we conclude that the moderate acid treatment can improve shown in Figure 7. Overall, the Young's modulus decreased slightly after acid oxidation; the decline is due to acid etching that removes microvoids and the amorphous outer layer from the carbon fibre surface [15]. Some researchers mentioned also another potential mechanism of the modulus variation: a change in the orientation of crystallites in CFs [19].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, these grooves and pits provide more bonding sites, increasing the interfacial adhesion. On the other hand, they introduce serious defects on the surface of carbon fibres, decreasing their tensile strength [15]. Post microbond test, samples were examined with FE-SEM to verify the location and mode of the failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly oriented graphitic planes are formed on the outer surface of carbon fibre by heat treatment during manufacture [53]. This highly aligned outer layer is typically 1.5 lm thick [53] and relatively weak [54,55], and removal of this layer can increase the tensile strength [56] and improve the interface strength in carbon fibre/epoxy systems [57]. It has also been suggested that the removal of the outer layer removes surface flaws, which are known to be a significant factor for tensile strength properties [56].…”
Section: The Effect Of Fibre Degradationmentioning
confidence: 99%
“…The chemical treatment approach utilizes acidic reagents (e.g., chlorosulfonic acid, nitric acid, etc.) to attach functional groups such as carboxyl, ether or hydroxyl to the fiber to improve the load transfer and adhesion between the fiber and the matrix . It was demonstrated that the chemical treatment improves the wettability and the surface roughness of the fibers which, in return, increases the tensile strength and the interlaminar shear strength of the composite .…”
Section: Introductionmentioning
confidence: 99%